2021
DOI: 10.1021/acsami.1c13524
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Bent-Angle Engineering for Tuning Topological Structures and Acetylene Purification Performances of Copper-Diisophthalate Frameworks

Abstract: To enrich structural chemistry and widen the application prospects of MOFs (metal−organic frameworks), the development of a synthetic strategy to realize structural and functional modulation is highly demanded. By implementation of the linker bent-angle engineering strategy, three banana-like diisophthalate linkers with distinct bent angles were designed and synthesized. The inclusion of the targeted linkers into MOFs through solvothermal assembly with CuCl 2 •2H 2 O under identical conditions yielded three cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 69 publications
(107 reference statements)
0
12
0
Order By: Relevance
“…As shown in Figure 3c, FUT-1a adsorbs more C 2 H 2 than CO 2 in the full pressure region, and the uptake capacity increases with the decreasing temperature. The C 2 H 2 adsorbed amounts of 153.7 and 120.2 cm 3 /g at 273 and 296 K, respectively, which is higher than those in many famous MOFs with excellent separation performance, such as UTSA-74a (108.2 cm 3 /g), 26 JCM-1(75.0 cm 3 /g), 27 FeNi-M′MOF (96.1 cm 3 /g), 28 CPL-1-NH 2 (41.2 cm 3 /g) 29 ATC-Cu (112.2 cm 3 /g), 30 ZJU-74a (85.7 cm 3 /g), 31 ZJNU-13 (118.4 cm 3 /g), 32 and slightly lower than those for FJU-90 (180.0 cm 3 /g), 25 SNNU-45 (134.0 cm 3 /g), 33 ZJNU-117 (153.1 cm 3 / g), 34 and ZJU-60a (150.6 cm 3 /g) 35 under ambient conditions. In addition, we found that one unit cell of FUT-1a can adsorb 88 C 2 H 2 molecules, which is very close to 94 adsorbed by one unit cell of HKUST-1 (201 cm 3 /g).…”
Section: Resultsmentioning
confidence: 88%
“…As shown in Figure 3c, FUT-1a adsorbs more C 2 H 2 than CO 2 in the full pressure region, and the uptake capacity increases with the decreasing temperature. The C 2 H 2 adsorbed amounts of 153.7 and 120.2 cm 3 /g at 273 and 296 K, respectively, which is higher than those in many famous MOFs with excellent separation performance, such as UTSA-74a (108.2 cm 3 /g), 26 JCM-1(75.0 cm 3 /g), 27 FeNi-M′MOF (96.1 cm 3 /g), 28 CPL-1-NH 2 (41.2 cm 3 /g) 29 ATC-Cu (112.2 cm 3 /g), 30 ZJU-74a (85.7 cm 3 /g), 31 ZJNU-13 (118.4 cm 3 /g), 32 and slightly lower than those for FJU-90 (180.0 cm 3 /g), 25 SNNU-45 (134.0 cm 3 /g), 33 ZJNU-117 (153.1 cm 3 / g), 34 and ZJU-60a (150.6 cm 3 /g) 35 under ambient conditions. In addition, we found that one unit cell of FUT-1a can adsorb 88 C 2 H 2 molecules, which is very close to 94 adsorbed by one unit cell of HKUST-1 (201 cm 3 /g).…”
Section: Resultsmentioning
confidence: 88%
“…4, Co-MOF 1 exhibits a typical type-I isotherm with a saturated uptake of 422.56 cm 3 g −1 for N 2 at 77 K and 1 bar, in agreement with the microporous nature of the framework. The Langmuir and Brunauer–Emmett–Teller surface areas 15 are calculated to be 1829.08 and 1620.64 m 2 g −1 based on N 2 adsorption at 77 K, respectively. (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent adsorption and separation ability of 1a for C 2 H 2 can be attributed to the strong interactions between the rich binding sites (uncoordinated N atoms and OMSs) in pores and C 2 H 2 . In addition, the critical temperatures of C 2 H 4 , C 2 H 6 , CH 4 , and CO 2 are lower than that of C 2 H 2 , which make C 2 H 2 more easily condensable than other gases and is also the possible factor for the high C 2 H 2 uptake of 1a …”
Section: Resultsmentioning
confidence: 99%